2021
DOI: 10.1038/s41598-021-84177-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different proportions of soft rock additions on organic carbon pool and bacterial community structure of sandy soil

Abstract: The sandy soil leaks water and fertilizer, and the ecological degradation is serious. The structural characteristics of soft rock and sandy soil are complementary, and the improvement of sandy soil by adding soft rock is of great significance to improve soil fertility, restore biodiversity, and maintain sustainable development of the Mu Us sandy land region. In this study, total organic carbon (TOC), particulate organic carbon (POC), dissolved organic carbon (DOC), easily oxidized organic carbon (ROC), microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…After ten years of tillage management, the SOC content of compound soils increased with increasing PSS application rates (Table 1). This is consistent with prior literature [7,36], which also found significantly higher fertility in compound soils with the addition of Pisha sandstone compared to sandy soil. This result can be explained as follows: on the one hand, the addition of PSS to sandy soil increased the presence of fine particles, and Ingelmo et al (2003) indicated that the soil organic matter (SOM) tended to concentrate around these fine particles, allowing for the formation of more organic-inorganic complexes [37].…”
Section: Responses Of Compound Soil Properties To Soft Rock Additionsupporting
confidence: 93%
“…After ten years of tillage management, the SOC content of compound soils increased with increasing PSS application rates (Table 1). This is consistent with prior literature [7,36], which also found significantly higher fertility in compound soils with the addition of Pisha sandstone compared to sandy soil. This result can be explained as follows: on the one hand, the addition of PSS to sandy soil increased the presence of fine particles, and Ingelmo et al (2003) indicated that the soil organic matter (SOM) tended to concentrate around these fine particles, allowing for the formation of more organic-inorganic complexes [37].…”
Section: Responses Of Compound Soil Properties To Soft Rock Additionsupporting
confidence: 93%
“…The porous structure of BC and FMBC provided an ideal habitat for soil microbes, and the microorganism metabolism and the efficiency of C utilization were improved, so part of the LOC was decomposed by microorganisms, which increased the DOC concentration (Meng et al 2018). The portion of soil C that is readily oxidized by KMnO 4 is referred to as the ROC (Li et al 2021b). Compared with control, the ROC concentration was significantly increased by 25.45-44.99% and 15.61-23.97% after adding BC and FMBC, respectively (P < 0.05), which may be related to the decomposition of easily oxidized components on the surface of biochar materials, as well as the increase in root exudates and microbial activity (Yang et al 2018).…”
Section: Effects Of Soil Toc Loc Fractions and Cmpi Under Different T...mentioning
confidence: 99%